Molecular Characterization of an Endopolygalacturonase from Fusarium oxysporum Expressed during Early Stages of Infection - García-Maceira, Fé I. (American Society for Microbiology, 2001)
The tomato vascular wilt pathogen Fusarium oxysporum f. sp. lycopersici produces an array of pectinolytic enzymes that may contribute to penetration and colonization of the host plant. Here we report the isolation of pg5, encoding a novel extracellular endopolygalacturonase (endoPG) that is highly conserved among different formae speciales of F. oxysporum. The putative mature pg5 product has a calculated molecular mass of 35 kDa and a pI of 8.3 and is more closely related to endoPGs from other fungal plant pathogens than to PG1, the major endoPG of F. oxysporum. Overexpression of pg5 in a bacterial heterologous system produced a 35-kDa protein with endoPG activity. Accumulation of pg5 transcript is induced by citrus pectin and d-galacturonic acid and repressed by glucose. As shown by reverse transcription-PCR, pg5 is expressed by F. oxysporum in tomato roots during the initial stages of infection. Targeted inactivation of pg5 has no detectable effect on virulence toward tomato plants.